Drugs and Police Response: Survey of Public Housing Residents in Denver, Colorado, 1989-1990 - Annan, Sampson O. ([Verlag nicht ermittelbar], 1995)
This data collection is the result of an evaluation of the NEPHU program, conducted by the Police Foundation under the sponsorship of the National Institute of Justice (NIJ). In August 1989, the Bureau of Justice Assistance supported a grant in Denver, Colorado, to establish a special Narcotics Enforcement in Public Housing Unit (NEPHU) within the Denver Police Department. The goal of the Denver NEPHU was to reduce the availability of narcotics in and around the city's public housing areas by increasing drug arrests. NEPHU's six full-time officers made investigations and gathered intelligence leading to on-street arrests and search warrants. The unit also operated a special telephone Drug Hotline and met regularly with tenant councils in the developments to improve community relations. The program worked in cooperation with the Denver Housing Authority and the uniformed patrol division of the Denver Police Department, which increased levels of uniformed patrols to maintain high visibility in the project areas to deter conventional crime. Using a panel design, survey interviews were conducted with residents in the Quigg Newton and Curtis Park public housing units, focusing on events that occurred during the past six months. Respondents were interviewed during three time periods to examine the onset and persistence of any apparent program effects. In December 1989, interviews were completed with residents in 521 households. In June 1990, 422 respondents were interviewed in Wave 2. Wave 3 was conducted in December 1990 and included 423 respondents. In all, 642 individuals were interviewed, 283 of whom were interviewed for all three waves. Because of the evaluation's design, the data can be analyzed to reveal individual-level changes for the 283 respondents who were interviewed on all three occasions, and the data can also be used to determine a cross-section representation of the residents by including the 359 "new" persons interviewed during the course of the evaluation. Information collected includes years and months lived in the development, assessments of changes in the neighborhood, whether the respondent planned to stay in the development, interactions among residents, awareness of anti-drug programs, ranking of various problems in the development, concerns and reports of being a victim of various crimes, perceived safety of the development, assessment of drug use and availability, assessment of police activity and visibility, and personal contacts with police. The unit of analysis is the individual.